2018
DOI: 10.4269/ajtmh.18-0014
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus: Knowledge Assessment of Residents and Health-Care Providers in Roatán, Honduras, following an Outbreak

Abstract: Few studies have evaluated the effectiveness of Zika virus (ZIKV) public health educational campaigns. Following a ZIKV educational campaign in Roatán, Honduras (October 2016), a survey was administered (March-May 2017) to residents ( = 348) and health-care professionals ([HCPs]; = 44) to evaluate ZIKV knowledge, attitudes, and preventive practices, with attention to sexual health. Knowledge scores were calculated and mapped using participants' home locations. The knowledge scores between HCPs and residents we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 12 publications
4
17
0
1
Order By: Relevance
“…This is consistent with the results of previous report in Bahrain and Indonesia, where only 39% of the nurses and 35% of HCP, respectively, were considered knowledgeable [14,16]. Besides, in Roatán, Honduras, only 14% of HCP knew that ZIKAV is sexually transmitted [13].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This is consistent with the results of previous report in Bahrain and Indonesia, where only 39% of the nurses and 35% of HCP, respectively, were considered knowledgeable [14,16]. Besides, in Roatán, Honduras, only 14% of HCP knew that ZIKAV is sexually transmitted [13].…”
Section: Discussionsupporting
confidence: 91%
“…Although 23.5% of the participating physicians perceived ZIKAV as a health threat to their patients, none of them had discussed or counseled a patient before regarding ZIKAV and its complications. Of note, physicians practice assessed by the study in Roatán concerned prevention of ZIKAV-sexual transmission by the physicians themselves, but not patient counseling practice [13]. Our results revealed that the most important factors for the adoption of the practice of patient counseling were the presence of an evidence of ZIKAV in Jordan or a recommendation by the CDC, the WHO, or the government.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…As reported before, in general, there are not many studies about arboviral diseases in Honduras [17][18][19][20][21], some explicitly exploring the potential impacts of climate change and variability on DENV, as well as the analysis of the 2015 DENV epidemics [9,12].…”
Section: Introductionmentioning
confidence: 99%